2002
DOI: 10.1016/s1074-7613(02)00302-3
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the p53-Effector Gene Gadd45a Develop a Lupus-Like Syndrome

Abstract: This study addresses the biological function of the p53-effector genes Gadd45a and p21 in the immune system. We find that Gadd45a is a negative regulator of T cell proliferation because, compared to wild-type cells, Gadd45a(-/-) T cells have a lower threshold of activation and proliferate to a greater extent following primary T cell receptor stimulation. Gadd45a(-/-) mice develop an autoimmune disease, similar to human systemic lupus erythematosus (SLE), characterized by high titers of anti-dsDNA, anti-ssDNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(142 citation statements)
references
References 24 publications
9
132
0
Order By: Relevance
“…Recent investigations have demonstrated that mice deficient for p21 exhibit lupus-like disease at 9 mo of age (65,66). However, it FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated that mice deficient for p21 exhibit lupus-like disease at 9 mo of age (65,66). However, it FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%
“…This enhances catalytic activity and subsequent autophosphorylation on the canonical activating residues Thr 180 /Tyr 182 (15). Lack of Gadd45␣ results in constitutively active T cell p38, hyperproliferation in response to TCR-mediated signals, and development of a lupus-like autoimmune disease (16,17). Because loss of Gadd45␣ results in spontaneous ZAP70-mediated T cell p38 activity (17) but decreased MAP kinase cascade-mediated p38 activity in stress or oncogeneactivated nonimmune cells (fibroblasts and keratinocytes; Refs.…”
Section: Gadd45␣ Regulates P38-dependent Dendritic Cell Cytokinementioning
confidence: 99%
“…17 Multiple types of human lymphoproliferative/autoimmune disease have been associated with increased incidence of lymphomas (reviewed in Ehrenfeld et al 18 ), and HTLVI infection can lead to both autoimmune disease and lymphoma. 19 Therefore, the presence of autoimmune disease in Gadd45aÀ/À mice may be a contributing factor to lymphomagenesis in the presence of additional tumor-promoting stimuli.…”
Section: Discussionmentioning
confidence: 99%